Sclerostin antibody enhances bone formation in a rat model of distraction osteogenesis. Issue 4 (1st February 2018) - McDonald, Michelle M.; Morse, Alyson; Birke, Oliver; Yu, Nicole Y. C.; Mikulec, Kathy; Peacock, Lauren; Schindeler, Aaron; Liu, Min; Ke, Hua Z.; Little, David G.
ABSTRACT: Neutralizing monoclonal sclerostin antibodies are effective in promoting bone formation at a systemic level and in orthopedic scenarios including closed fracture repair. In this study we examined the effects of sclerostin antibody (Scl‐Ab) treatment on regenerate volume, density, and strength in a rat model of distraction osteogenesis. Surgical osteotomy was performed on 179 Sprague Dawley rats. After 1 week, rats underwent distraction for 2 weeks, followed by 6 weeks for consolidation. Two treatment groups received biweekly subcutaneous Scl‐AbIII (a rodent form of Scl‐Ab; 25 mg/kg), either from the start of distraction onward or restricted to the consolidation phase. These groups were compared to controls receiving saline. Measurement modalities included longitudinal DXA, ex vivo QCT, and microCT, tissue histology, and biomechanical four‐point bending tests. Bone volume was increased in both Scl‐Ab treatments regimens by the end of consolidation (+26–38%, p  < 0.05), as assessed by microCT. This was associated with increased mineral apposition. Importantly, Scl‐Ab led to increased strength in united bones, and this reached statistical significance in animals receiving Scl‐Ab during consolidation only (+177%, p  < 0.01, maximum load to failure). These data demonstrate that Scl‐Ab treatment increases bone formation, leading to regenerates with higher bone volume and improved strength. Our data also suggest that the optimal effects of Scl‐Ab treatment are achieved in the latter stages of distraction osteogenesis. These findings support further investigation into the potential clinical application of sclerostin antibody to augment bone distraction, such as limb lengthening, particularly in the prevention of refracture. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1106–1113, 2018.